2004
DOI: 10.1002/eji.200324504
|View full text |Cite
|
Sign up to set email alerts
|

NKp46 defines a subset of bovine leukocytes with natural killer cell characteristics

Abstract: Natural killer (NK) cells have not previously been precisely identified or characterized in cattle or any other ruminant species. We have generated a monoclonal antibody against bovine NKp46, which is expressed exclusively by NK cells in man. NKp46 + cells comprised 1-10% of blood mononuclear cells in cattle, and did not stain with antibodies against CD3, CD4, TCR1, B cell or granulocyte markers. The majority of the NKp46 + cells expressed CD2, and a variable fraction also expressed CD8. The tissue distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
134
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(148 citation statements)
references
References 35 publications
12
134
1
1
Order By: Relevance
“…The involvement of CD8 T cells was inferred from ablation of cytotoxicity following depletion of CD8 T cells by antibody-and complementmediated lysis. Since CD8 is also known to be expressed on bovine NK cells and gd T cells [36,37], which can exhibit cytotoxic activity, the attribution of the cytotoxicity measured in these studies to classical CD8 T cells remains open to question. Nevertheless, it is possible that CD8 T cells specific for additional antigens, including the glycoproteins, were present at low frequency in our T-cell lines, but were not detected by our screening method.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of CD8 T cells was inferred from ablation of cytotoxicity following depletion of CD8 T cells by antibody-and complementmediated lysis. Since CD8 is also known to be expressed on bovine NK cells and gd T cells [36,37], which can exhibit cytotoxic activity, the attribution of the cytotoxicity measured in these studies to classical CD8 T cells remains open to question. Nevertheless, it is possible that CD8 T cells specific for additional antigens, including the glycoproteins, were present at low frequency in our T-cell lines, but were not detected by our screening method.…”
Section: Discussionmentioning
confidence: 99%
“…The CD2 molecule is the receptor for activation on both T cells and NK cells (McNerney & Kumar 2006), although it is not expressed on most WC1+ γδT cells (Davis et al 1996). Storset et al (2004) reported that in cattle, most circulating NK cells are CD2+ and that CD2-cells comprise a low percentage. In this study, only the smaller CD2-NK cell population increased significantly just after transport, as did the total NK cell population.…”
Section: Discussionmentioning
confidence: 99%
“…NKp 46 gene is currently considered the most reliable identifying marker for natural for natural killer cells across species [16]. Natural Killer cells are effector regulatory lymphocytes of the innate immune system that contribute to tumor surveillance hematopoietic allograft rejection, control of microbial infections and pregnancy [17]. They have also been suggested to provide a link between innate and acquired immunity through production of cytokines and interaction with antigen -presenting cells [17].…”
Section: Nkp 46 Genementioning
confidence: 99%
“…Natural Killer cells are effector regulatory lymphocytes of the innate immune system that contribute to tumor surveillance hematopoietic allograft rejection, control of microbial infections and pregnancy [17]. They have also been suggested to provide a link between innate and acquired immunity through production of cytokines and interaction with antigen -presenting cells [17]. Since the NKp 46 gene is thought to be the main natural killer cell activating receptor and also proven to display functional cross talk with other natural cytotoxic receptors and natural killer cell activating receptors, we propose a strong involvement of this gene in the pathogenesis of unexplained recurrent miscarries suggesting it a candidate gene for the condition [18].…”
Section: Nkp 46 Genementioning
confidence: 99%